2019
DOI: 10.4236/ojapps.2019.93012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hypertension, Diabetes and Obesity among Lecturers and Support Staff of Bishop Stuart University in Mbarara, Uganda

Abstract: Aim: To establish the prevalence and risk factors for hypertension, diabetes and obesity among teaching and non-teaching staff of Bishop Stuart University, Mbarara-Uganda. Background: None communicable diseases (NCDs) are projected to exceed communicable diseases as the most common causes of death by 2030 in Africa. Most sub-Saharan African countries however lack detailed countrywide data on hypertension and other NCDs risk factors. Cognizant of Uganda's recent inclusion of Hypertension and diabetes in the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
(16 reference statements)
4
5
0
1
Order By: Relevance
“…Diabetes was also high in patients who were overweight (33.3%). e findings support other studies which have reported that there is a high chance of developing diabetes in overweight and obese people [15,42,43] and hence, a greater chance of developing diabetic retinopathy. Rustom et al [16] also indicated that hypertension is associated with overweight among the military population in Bangladesh.…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes was also high in patients who were overweight (33.3%). e findings support other studies which have reported that there is a high chance of developing diabetes in overweight and obese people [15,42,43] and hence, a greater chance of developing diabetic retinopathy. Rustom et al [16] also indicated that hypertension is associated with overweight among the military population in Bangladesh.…”
Section: Discussionsupporting
confidence: 90%
“…From the study, the overall prevalence of hypertension amongst the participants was 6.7%. The prevalence found in this study was much lower than the 21.3% reported in Port-Harcourt, South-South Nigeria (Ordinioha, 2013) but very close to the study conducted in among lecturers in Mbarara Uganda in which prevalence was found to be 7.7% (Amanyire et al, 2019). In contrast, a higher prevalence of 52% among lecturers in Dhaka, Bangladesh (Barua et al, 2018), and 44% at Hawassa University in Ethiopia (Esaiyas et al, 2018).The lower prevalence of hypertension found in this study may be due to the fact that the participants exhibited good health-seeking behavior and good lifestyle.…”
Section: Discussionsupporting
confidence: 71%
“…(Ayob, Abdul Hamid, Mohd Daud ve Sean, 2019). Uganda'da üniversite öğretim elemanları ile gerçekleştirilen bir çalışmada ise akademisyenlerin %28'nin obez olduğu bulunmuştur (Amanyire, Tumwebaze, Mugisha, ve Bright, 2019). Yine Suudi Arabistan'da yapılan bir çalışmada obez tıp okutmanlarının sayısı önemli ölçüde yüksek bulunmuştur (Alfagi et al 2016).…”
Section: Discussionunclassified